2023
DOI: 10.1186/s40813-022-00297-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carcass quality, body and pulmonary lesions detected at the abattoir in heavy pigs subjected or not to tail docking

Abstract: Background Nowadays, body and tail lesions and respiratory disease are some of the greatest problems affecting the health and welfare of pigs. The aim of the study was to measure the prevalence of pleurisy, bronchopneumonia (enzootic pneumonia like lesions) and lesions on tail and body of heavy pigs subjected or not to tail docking through the inspection in Italian abattoirs. Additionally, the effect of tail docking and season was investigated on carcass quality (weight, % of lean meat, and Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
1
1
Order By: Relevance
“…Our study shows an underestimation of APP infections by the SPES system considering the high number of samples with a score 0, but on the contrary with positive APP identification. This study reported a different situation in pig farms caused by APP infections, in comparison with other Italian studies investigating pulmonary lesions at slaughterhouses [23,24]. Literature shows lower SPES scores (from a minimum of 0.79 to a maximum of 0.97) for the investigated carcasses, than our study reporting an average SPES value of 1.74.…”
Section: Discussioncontrasting
confidence: 86%
“…Our study shows an underestimation of APP infections by the SPES system considering the high number of samples with a score 0, but on the contrary with positive APP identification. This study reported a different situation in pig farms caused by APP infections, in comparison with other Italian studies investigating pulmonary lesions at slaughterhouses [23,24]. Literature shows lower SPES scores (from a minimum of 0.79 to a maximum of 0.97) for the investigated carcasses, than our study reporting an average SPES value of 1.74.…”
Section: Discussioncontrasting
confidence: 86%
“…All of these issues can result in poor health status, which may require vet intervention, lead to low quality of meat products, reduced weight gain, and even death of the affected individual. In summary, these problems can cause economic losses in both farms and slaughterhouses (Telkanranta et al 2014;Henry et al 2021;Gomes et al 2022;Amatucci et al 2023).…”
Section: Introductionmentioning
confidence: 99%